Answer:
Explanation:
Simplifying
6 = 1 + -2n + 5
Reorder the terms:
6 = 1 + 5 + -2n
Combine like terms: 1 + 5 = 6
6 = 6 + -2n
Add '-6' to each side of the equation.
6 + -6 = 6 + -6 + -2n
Combine like terms: 6 + -6 = 0
0 = 6 + -6 + -2n
Combine like terms: 6 + -6 = 0
0 = 0 + -2n
0 = -2n
Solving
0 = -2n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '2n' to each side of the equation.
0 + 2n = -2n + 2n
Remove the zero:
2n = -2n + 2n
Combine like terms: -2n + 2n = 0
2n = 0
Divide each side by '2'.
n = 0
Simplifying
n = 0